Transforming everyday experience: Transformative learning, disorienting dilemmas and Honneth's theory of recognition. (23rd June 2022) - Fleming, Ted
Abstract: Axel Honneth's theory of recognition outlines the personal and social contexts of family, law and community solidarities in which recognition – and misrecognitions – are experienced. His work has implications for Mezirow's theory of transformative learning. Transformative learning is critiqued for an over dependence on the Dewey/Habermas foundations that demand high levels of rationality and for an over reliance on individual learning to the exclusion of social learning. Honneth's ideas are explored in order to further develop the understanding of how experience is central to transformative learning. Disorienting dilemmas and the perplexities that lead to transformative learning are reinterpreted as experiences that have personal and social dimensions. Experience – often seen as individual and unique ‐ cannot be disconnected from social contexts. Honneth helps us resolve these issues and allows us to re‐interpret transformative learning as the transformation of experience. Finally, two further concepts are introduced: a) the dialectic nature of experience (Negt); and b) the importance of completeness (Negt). These further enhance the experiential grounding for emancipation and the emancipatory project of transformative learning.